THE HEGEMONY IMPOSED BY THE GOVERNMENT AND THE RESISTANCE OF WETU TELU SASAKNESE ETHNIC GROUP AT BAYAN DISTRICT, NORTH LOMBOK REGENCY - Wirata, I Wayan; Parimartha, I Gde; Suastika, I Made; Subagiasta, I Ketut (E-Journal of Cultural Studies, 2010)
This research is entitled “The Hegemony Imposed by the Government and theResistance of Wetu Telu Sasaknese Ethnic Group at Bayan District, North Lombok”.The interaction between the government and the Wetu Telu Sasaknese community atBayan District has resulted in differences in views, ideas, and behaviors leading tofriction and refusal or opposition from the community.This research is focused on 1) how has the hegemony imposed by thegovernment upon the Wetu Telu Sasaknese Ethnic Group residing at Bayan District,North Lombok Regency taken place? 2) what has been done by the people of the WetuTelu Sasaknese Ethnic Group residing at Bayan Distrik, North Lombok to resist to thehegemony imposed by the government upon them? and 3) what are the effects andmeanings of the hegemony imposed by the government and the resistance of the WetuTelu Sasaknese Ethnic Group on the multicultural community life at Bayan District,North Lombok Regency?The data needed were collected by interview, observation, and documentationand were descriptively, qualitatively and interpretatively analyzed. The theories used togive answers to the problems formulated above are the theory of hegemony (Gramsci),the theory of deconstruction (Jacques Derrida), and the theory of discourse (Foucault).The results show that the hegemony imposed by the government has taken placein a number of particular aspects such as the religious aspect, socio political aspect,cultural aspect and educational aspect. Being marginalized and being not free indeveloping their tradition and culture, the people of Wetu Telu Sasaknese Ethnic Groupresiding at Bayan District, North Lombok Regency, have been responsible for theirresistance to the government and the followers Islam Waktu Lima. The resistance hasbeen shown by avoiding, refusing and even opposing what is considered not inaccordance with their tradition and culture.One of the effects of the hegemony imposed by the government and theresistance made by the people of the Wetu Telu Sasaknese Ethnic Group residing atBayan District is that there has been imbalanced communication between the followersof Islam Waktu Lima (which collaborates with the government) and the Wetu TeluSasaknese Ethnic Group residing at Bayan District leading to a social conflict. The othereffects have been that such a social conflict has disturbed the social life of the community, has led to a paradox of cultural preservation, and has narrowed the power ofthe Wetu Telu Sasaknese Ethnic Group residing at Bayan District. From the meaningpoint of view, what has taken place at Bayan District has philosophical and multiculturalmeaning as well as the meanings of struggle for identity, cultural preservation anddynamism.